2020
DOI: 10.1038/s41598-020-69463-4
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature optical properties of indium tin oxide thin-films

Abstract: Indium tin oxide (ITO) is one of the most widely used transparent conductors in optoelectronic device applications. We investigated the optical properties of ITO thin films at high temperatures up to 800 °C using spectroscopic ellipsometry. As temperature increases, amorphous ITO thin films undergo a phase transition at ~ 200 °C and develop polycrystalline phases with increased optical gap energies. The optical gap energies of both polycrystalline and epitaxial ITO thin films decrease with increasing temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…The DC sweep allows extended period for long range atomic diffusion, during which the atoms can settle in the most energetically favorable positions. The red shift is a result of PCM phase transition because it was found that the refractive index of amorphous ITO remains relatively constant upon heating up to 773 K [ 51 ] while the thermo‐optic effect is volatile. The spectral shift of 0.4 nm matches very well with the predicted shift of 0.39 nm based on simulation of rib waveguide (see Section S4, Supporting information) but lower than what was measured from fully etched waveguide (0.48 nm) due to less mode confinement.…”
Section: Resultsmentioning
confidence: 99%
“…The DC sweep allows extended period for long range atomic diffusion, during which the atoms can settle in the most energetically favorable positions. The red shift is a result of PCM phase transition because it was found that the refractive index of amorphous ITO remains relatively constant upon heating up to 773 K [ 51 ] while the thermo‐optic effect is volatile. The spectral shift of 0.4 nm matches very well with the predicted shift of 0.39 nm based on simulation of rib waveguide (see Section S4, Supporting information) but lower than what was measured from fully etched waveguide (0.48 nm) due to less mode confinement.…”
Section: Resultsmentioning
confidence: 99%
“…Figure b is a time series of the PL spectra of AuBP 1 acquired with 530 nm excitation over a time period of 50 s. The intensity of the spectrum is stable over a long time period, while the peak of the PL spectra blue-shifts from 704 to 700 nm according to Lorentzian fits. This slight blue-shift could be a thermal effect due to the change of the refractive index caused by continued laser excitation . The thermal effect or damage to the AuBP is unlikely to be responsible for the ∼10 nm difference between the dark-field scattering and LPR-induced emission excited at 488 and 530 nm, however, as the PL spectrum using 633 nm excitation is acquired after the short-wavelength excitation.…”
Section: Resultsmentioning
confidence: 97%
“…Nevertheless, in this study thermal energy necessary for crystallization was dissipated by short pulse durations [ 57 ]. ITO thin films undergo an amorphous—polycrystalline phase transition at ~200 °C [ 58 ], which increases optical and electrical properties [ 59 ]. On the other hand, amorphous structure can be desirable due to solving ITO etching residue problems in large-size 3D display devices [ 60 ].…”
Section: Resultsmentioning
confidence: 99%